Copper-catalyzed asymmetric arylation of N-heteroaryl aldimines : elementary step of a 1,4-insertion - Wu, Chunlin (2021)
Copper complexes of monodentate phosphoramidites efficiently promote asymmetric arylation of N-azaaryl aldimines with arylboroxines. DFT calculations and experiments support an elementary step of 1,4-insertion in the reaction pathway, a step in which an aryl-copper species adds directly across four atoms of C=N-C=N in the N-azaaryl aldimines.